The Effect of Creative Dance Based on Identity Elements on Motor Development in Early Childhood Education - Fitriani Fitriani; Rani Puspa Juwita (STAI Publisistik Thawalib Jakarta, 2026)
Gross motor development is an important aspect of early childhood growth, yet in many early childhood education institutions, motor stimulation remains limited and suboptimal. One potential medium is creative dance based on identity elements, as it can integrate physical movement, rhythm, and creative expression in an enjoyable way. This study aimed to examine the effect of creative dance based on identity elements on the motor development of children at Semayang Ni Ine Bintang early childhood education. The research problem arose because some children were unable to perform gross motor movements in a coordinated and independent manner in response to the teacher’s cues and demonstrations. The method employed a quantitative, experimental design in which the experimental group received a creative dance intervention, and motor skills were measured before and after the intervention. Data analysis using a paired sample t-test showed a significant difference between pre-test and post-test scores (p = 0.001 < 0.05), indicating a positive effect of creative dance on children’s motor skills. The study concludes that creative dance based on identity elements is effective in enhancing gross motor development in early childhood. The significance of this research lies in providing an innovative learning model that not only optimizes physical abilities but also encourages creativity and active engagement in the learning process.